(untitled) - Webber, Roger (Cambridge, MA., 2005)
Communicable diseases are community problems, which can devastate whole populations, in both developing and developed countries. Epidemiology is the science of communities that looks at many individuals to try and discover common features in them. From this analysis the cause and characteristcics of a disease can be worked out. The first chapters of this book look at communicable disease theory and formulating common principles in both epidemiology and control. Since the first edition a new section on climate change due to global warming and its effect on disease as been added. Later chapters cover various criteria of communicable diseases including more recent outbreaks that have emerged since the first edition and others which many become important in the future. This book will prove an essential tool for doctors, epidemiologists and those working in the control of communicable disease, as well as providing a clear introduction for medical students, public health specialists and those involved in disease control.
Keywords: Communicable diseases,Communicable diseases; Epidemiology,Prevention